Oligo-Carrageenans Enhance Growth and Contents of Cellulose, Essential Oils and Polyphenolic Compounds in Eucalyptus Globulus Trees - Moenne-Munoz, A; Contreras-Arredondo, R; Gonzalez-Figueroa, A (2013)
Eucalyptus globulus (Myrtaceae) originated in Australia and has been introduced in countries with temperate weather in order to obtain wood for cellulose extraction and building purposes. In this work, we analyzed the potential stimulation of growth in height and trunk diameter as well as the content of holo-cellulose, ?-cellulose (long cellulose chains), essential oils and polyphenolic compounds (PPCs) in E. globulus trees treated with oligo-carrageenans (OCs) kappa, lambda and iota, at 1 mg mL-1, once a week, four times in total and then cultivated for three additional years without further treatment. Eucalyptus treated with OCs kappa, lambda and iota showed an increase in height, mainly with OCs kappa and iota by 58% and 47%, respectively, and in trunk diameter by 44% and 40%, respectively. In addition, OCs induced an increase in the contents of holo-cellulose and ?-cellulose, mainly OCs kappa and iota which increased holo-cellulose by 8% and 5%, respectively, and ?-cellulose by 16 and 13%, respectively. Moreover, OCs increased the content of essential oils, mainly OCs kappa and iota by 67% and 39%, respectively. Furthermore, OCs decreased the concentration of total phenolic compounds but differentially changed the concentration of several PPCs such as genistein, rutin, ellagic acid, morin, luteolin and quercetin with potential antimicrobial activities. Thus, marine algae OCs kappa, lambda and iota stimulate growth of E. globulus trees by enhancing height and trunk diameter as well as the content of ?-cellulose, total essential oils, and some PPCs with potential antimicrobial activities. © 2013 by the authors; licensee MDPI, Basel, Switzerland.